2020
DOI: 10.1002/ange.202007224
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Lithography Hydrodynamic Printing of Micro/Nanostructures on Curved Surfaces

Abstract: A key issue of micro/nano devices is how to integrate micro/nanostructures with specified chemical components onto various curved surfaces. Hydrodynamic printing of micro/nanostructures on three‐dimensional curved surfaces is achieved with a strategy that combines template‐induced hydrodynamic printing and self‐assembly of nanoparticles (NPs). Non‐lithography flexible wall‐shaped templates are replicated with microscale features by dicing a trench‐shaped silicon wafer. Arising from the capillary pumped functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The conformal fabrication of thin film structure is of vital importance in enabling novel structure-property relationships ( 6 ) by fulfilling dedicated geometries for the robust sensing performances of flexible electronics ( 7 ). The versatile construction of two-dimensional (2D) micro-/nanostructures is highly desirable in designing and developing advanced electronic and optical devices with outstanding characteristics and functionalities ( 8 ). Several technologies are well established for achieving conformal 2D thin film patterning either in benchtop process or in scale-up manufacturing, such as subtractive lithography, laser direct writing, and transfer printing ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The conformal fabrication of thin film structure is of vital importance in enabling novel structure-property relationships ( 6 ) by fulfilling dedicated geometries for the robust sensing performances of flexible electronics ( 7 ). The versatile construction of two-dimensional (2D) micro-/nanostructures is highly desirable in designing and developing advanced electronic and optical devices with outstanding characteristics and functionalities ( 8 ). Several technologies are well established for achieving conformal 2D thin film patterning either in benchtop process or in scale-up manufacturing, such as subtractive lithography, laser direct writing, and transfer printing ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the integration of Fabry-Pérot-random, distributed feedback-random, and WGM-random cavities have been reported consecutively. [35][36][37][38][39][40][41] Among these, WGM lasing from total internal reflection has been efficiently achieved with a low threshold. 42 For instance, Nie et al reported a dye-doped polystyrene-encapsulated silica-glass capillary, in which a strong WGM resonance in the capillary helps the generation of coherent RL when the refractive index of the filling medium is greater than that of the glass capillary.…”
Section: Introductionmentioning
confidence: 99%